Remarks on the Origin of All-Inclusive Pervasion - Shiga, Kiyokuni (Journal of Indian philosophy, 2011)
Previous studies have claimed that the term 'all-inclusive pervasion' (sarvopasaṃhāravyāpti) appeared for the first time in the Hetubindu, and that it was Dharmakīrti who created this theory. This article attempts to modify this view and to show that the prototype of this theory can already be found in Dignāga's system of logic. Dignāga states in the third chapter of the Pramāṇasamuccayavṛtti that the co-existence of a logical reason with what is to be proved is understood by means of two types of exemplification that sum up external items (bāhyārthopasaṃhṛta). Furthermore, with respect to where the pervasion is indicated, he states in the second chapter of the same work that the non-deviation of a logical mark from what is to be proved is indicated elsewhere (anyatra). He also implies that anyatra means in the substratum in general (ādhārasāmānya) and that the subject is implicitly included in other substrata, i.e., in the substratum in general. Building upon Dignāga's awareness of the issue, the conflict between the universality of pervasion and the particularity of actual inference, Dharmakīrti reinforced Dignāga's system of logic by demonstrating that a property to be proved as the universal is not particularised by the subject by the use of the idea of 'the exclusion of non-connection' (ayogavyavaccheda) and by adopting the concept of 'all' in place of 'external items'.